Analysis of the Role of Administrative Staff in Supporting the Smooth Operation of Junior High School Administration - Elmiyatus Sakdiyah (Southeast Asian Journal of Global Trends and Issues in Education, 2026)
Background: This study is grounded in the importance of school administration as a key support for the effectiveness of educational processes, in which administrative staff play a strategic role in ensuring smooth operational activities. Objective: The objective of this study is to analyse the role of administrative staff in supporting school administration at SMPN 1 Jambesari and to identify the challenges and strategies implemented. Method: This study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and analysed using the Miles and Huberman model. Results: The findings indicate that administrative staff play a significant role in managing student data, handling correspondence, maintaining archives, and providing administrative services for teachers and students. However, several challenges were identified, including limitations in human resources, infrastructure, and technological competence. Conclusion: The study concludes that administrative staff play a vital role in supporting the effectiveness of school administration, despite facing various constraints. Contribution: This study provides practical recommendations for improving the quality of administrative services through capacity building and optimising technology use.